أوجه الشبه والاختلاف بين العربية والإندونيسية في ظاهرة الترادف – وكيفية التعامل مع هذه الظاهرة عند تدريس العربية للإندونيسيين - Yenni Patriani (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2018)
Abstract This research is about "similarities and differences between Arabic and Indonesian in the phenomenon of tandem - and how to deal with this phenomenon in teaching Arabic to Indonesians." The importance of Arabic is also reflected in the fact that is the key of Islamic and Arab culture. It allows learner to learn about the cultural and intellectual dimensions of a nation that has been crowned on the throne for centuries. It has left a great cultural heritage in various arts and sciences.The importance of Arabic stems from the fact that it is one of the strongest links and links between Muslims. Language is one of the most important elements of unity among Islamic societies. Arabic is no longer a language specific to Arabians, but has become a universal language for millions of Muslims in the world today demand for their connection to their religion and Islamic culture. We also see a desire to learn the arabic language for non-Muslims to communicate with the people of the language on the one hand and to communicate with the Arab and Islamic heritage on the other.Features of Arabic Tandem. It is an important factor in the growth of language, two words or more that indicate one meaning. We can use it without separating them. The speaker observes the exact order in the choice of the word of the synonyms corresponding to the sentence.It is interesting that Arabic is the only language that gives citizenship to anyone who speaks it. "Whoever learns Arabic is an Arabian."There is almost unanimous agreement that tandem is one of the reasons for the richness of language in vocabulary, whether it is Arabic, Indonesian, or other languages. And its privilege with a wealth of words. There have been many works that collected the vocabulary of this phenomenon in the ancients in particular, which reinforces this statement to the extent that it is surprising, such as the names of one thing to thousands of words.